Our posthuman lingo. - McFedries, P.
The English language is preparing for a radical revision of what we call human following the developments in biomedical engineering such as: the possibility of torso fat and rib bones rejiggered to form angel-like alar appendages; cochlear implants enabling some deaf people to hear and which may soon be used to enhance normal hearing; and an arm implanted with a chip that communicated via RF with sensors scattered around the building enabling doors to open and lights to turn on automatically whenever the subject approached. The author describes the meanings of words used to describe these areas such as: cyborg, neomorph, homomorph and ultrahumans amongst others.
Keywords: Biomedical engineering; Posthuman language